Przyczynek do badań nad szlachtą ruską w wielkim księstwie litewskim. Część I: protoplaści rodu Woyniłłowiczów (koniec XV i XVI w.) - Augusiewicz, Sławomir (Przegląd Wschodnioeuropejski, 2022)
There is a growing demand amongst historians for an increasing number of studies (amongst them genealogical ones) about Ruthenian noble families in the Grand Duchy of Lithuania. One of such families was the Woyniłłowicz family, coming from Hospodar’s nobility, who settled at the end of the 15th century near Nowogródek. In the second half of the 16th century the family had already grown – at that time the lands of Klukowicze and Niańków were in their possession. From this period came one of the most distinguished figures in the family, who gave rise to several Woyniłłowicz’s ancestral lines, which continued throughout the 19th and 20th centuries.